Research trends e-module development in SINTA indexed Indonesian journal of biology education 2: A literature review - Ainanur Fauziyah Almaas; P. Paidi; M. Mualimin; Tatag Bagus Putra Prakarsa (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
One of the educational resources that Indonesia has produced extensively is e-modules. It is still necessary to investigate and assess e-module development research. Analysis of e-module development publications in Indonesian biology education journals is the goal of this assessment of the literature. Only the JPBI (Jurnal Pendidikan Biologi Indonesia), BIOSFER (Journal of Biology Education), and Biolokus (all 2022–2024) editions of the SINTA 2 biology education publications are included in this study. "Module" is the keyword used to retrieve a list of indexed articles from the three journals. Out of the hundreds of articles gathered, 13 were found once the article collection procedure was finished. According to the study's findings, researchers primarily select R&D based on the requirements of creating biology learning e-modules. Furthermore, the most frequently used research design is the R&D development model; the most frequently used research instrument is a questionnaire; the most frequently used data analysis technique is N-gain and qualitative and quantitative descriptive analysis; the most frequently used research location is Java Island; the most frequently chosen research subjects are others include experts; the most frequently chosen materials are environmental change. Therefore, more thorough and in-depth research is still required about e-module development.